Type II Grass Carp Reovirus Infects Leukocytes but Not Erythrocytes and Thrombocytes in Grass Carp (Ctenopharyngodon idella) - Yang, Ling (Viruses, 2021)
Grass carp reovirus (GCRV) causes serious losses to the grass carp industry. At present, infectious tissues of GCRV have been studied, but target cells remain unclear. In this study, peripheral blood cells were isolated, cultured, and infected with GCRV. Using quantitative real-time polymerase chain reaction (qRT-PCR), Western Blot, indirect immunofluorescence, flow cytometry, and transmission electron microscopy observation, a model of GCRV infected blood cells in vitro was established. The experimental results showed GCRV could be detectable in leukocytes only, while erythrocytes and thrombocytes could not. The virus particles in leukocytes are wrapped by empty membrane vesicles that resemble phagocytic vesicles. The empty membrane vesicles of leukocytes are different from virus inclusion bodies in C. idella kidney (CIK) cells. Meanwhile, the expression levels of IFN1, IL-1β, Mx2, TNFα were significantly up-regulated in leukocytes, indicating that GCRV could cause the production of the related immune responses. Therefore, GCRV can infect leukocytes in vitro, but not infect erythrocytes and thrombocytes. Leukocytes are target cells in blood cells of GCRV infections. This study lays a theoretical foundation for the study of the GCRV infection mechanism and anti-GCRV immunity.